2012
DOI: 10.1590/s0102-09352012000400011
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and thermoregulatory effects of xylazine-ketamine mixture persist even after the anesthetic stage in rats

Abstract: The xylazine-ketamine mixture (KX) is an anesthetic approach commonly administered to assess cardiovascular function in rodents. This study aimed to examine if the cardiovascular and thermoregulatory effects of KX could persist after the anesthetic state ceased in rats. Male Wistar rats were anesthetized with K (50mg/kg) X (10mg/kg) through the intra-peritoneal route. Hemodynamic and thermoregulatory repercussions were evaluated in animals in awake state, during an anesthetic depth and after complete recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 8 publications
4
14
0
2
Order By: Relevance
“…Although the combination of KX should therefore not lead to a marked hypotension, BP continuously decreased over a long time to mild hypotensive values almost until the rats had regained their righting reflex. These findings are in accordance with another study, which showed the most prominent hypotension after 150 minutes of KX anaesthesia in rats [ 50 ]. In contrast, MMF had a completely different effect on BP.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although the combination of KX should therefore not lead to a marked hypotension, BP continuously decreased over a long time to mild hypotensive values almost until the rats had regained their righting reflex. These findings are in accordance with another study, which showed the most prominent hypotension after 150 minutes of KX anaesthesia in rats [ 50 ]. In contrast, MMF had a completely different effect on BP.…”
Section: Discussionsupporting
confidence: 93%
“…With KX, the lowest HR was observed after 30 minutes followed by a continuous, slow increase of HR almost until the end of the measurement. One study described similar findings of alterations in HR during KX anaesthesia in rats and it was suggested that the cardiovascular depressant effect of xylazine overrides the increased sympathetic and reduced vagal tone and the adverse effect of baroreceptor reflex attributed to ketamine [ 50 ]. HR during MMF rapidly decreased after injection and continued to decrease slightly until it was antagonized.…”
Section: Discussionmentioning
confidence: 86%
“…This explanation is further supported by previous literature describing dramatic reductions in mean arterial pressure in rodents after ketamine-xylazine anesthesia; with some papers describing these effects continuing beyond the recovery period. 2,43 Further mechanistic research is necessary to confirm this speculation.…”
Section: Discussionmentioning
confidence: 99%
“…Rats in our experiments were left spontaneously breathing, without intubation and without accessory oxygen as described several times for KX narcosis [14–16]. We observed unsustainable high mortality rates during the first 7 postoperative days but not during or immediately after surgery.…”
Section: Introductionmentioning
confidence: 98%